Structuring A Successful Information Technology Transfer Process: A Case Study from the Perspectives of Actor Network Theory - Ibrahim, Huda; Kasimin, Hasmiah (Universiti Utara Malaysia Press, 2010)
An efficient and effective information technology transfer from developed countries to Malaysia is an important issue as a prerequisite to support the ICT needs of the country to become not only a ICT user but also a ICT producer. One of the factors that influences successful information technology transfer is managing the process of how technology transfer occurs in one environment. It involves managing interaction between all parties concerned which requires an organized strategy and action toward accomplishing technology transfer objective in an integrated and effective mode. Using a conceptual framework based on the Actor Network Theory (ANT), this paper will analyse a successful information technology transfer process at a private company which is also a supplier of information technology (IT) products to the local market. This framework will explain how the company has come up with a successful technology transfer in a local environment. Our study shows that the company had given interest to its relationships with all the parties involved in the transfer process. The technology transfer programme and the strategy formulated take into account the characteristics of technology and all those involved.